The effects of group logo-therapy on life expectancy and sleep quality in elderlies of boarding center of Tehran city - Fatemeh Suzan Famil Ahmarian; Anahita khodabakhshi koolaee; Mohammad Reza Falsafinejad (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Background and Objectives: Hope plays an important role in coping with psychological and biological problem in different stages of life, especially in elderly stage.  Therefore, the aim of current research is investigation of the efficacy of group logo-therapy in hope and sleep quality in elderlies. Materials and Methods: This research is a quasi-experimental study with pre and post- tests. The study population was Seoul Center and 30 elderlies were selected through the criteria. They were assigned randomly to the control and experimental groups. The experimental group received logo therapies for 10 treatment sessions (75 min for each session per week). Statistical analyses were conducted by t-dependent test and analysis of covariance. The research instruments were Pittsburgh Sleep Quality Index, Miller Hope Scale, and Mini Mental State examination. Results: There is significantly difference in life expectancy between elderlies in pre and post test. There is not significantly difference between mean's scores of sleep quality's elderlies in pre and post-tests(p<0.05). Conclusion: The results indicated that logo-therapy has a significantly influence on increasing the hope in life among elderlies. So, it can be considered as a therapeutic intervention in psychological problems related to lack of meaning and hope in the life. Keywords:Group Counseling, Logo-therapy, life expectancy, Sleep Quality, Elderlies For downloading the full-text of this article please click here.